The Role of Islamic Religious Education in Shaping Sharia Business Ethics among the Millennial Generation: Evidence from Urban Indonesia - Lailal Karmila; Novita Eka Paradina; Isti Fajri Khairunnisa (The Future of Education Journal, 2025)
This study aims to analyze the role of Islamic Religious Education (IRE) in shaping Sharia business ethics among the millennial generation and to identify effective mechanisms for value internalization within the context of the digital economy. Employing an explanatory sequential mixed-methods design, the study involved 384 millennial respondents (aged 25–40 years) working as entrepreneurs or professionals in the creative economy and Islamic finance sectors across three major urban areas in Indonesia. The quantitative phase was complemented by in-depth interviews and focus group discussions (FGDs) with 15 participants. Quantitative data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), while qualitative data were examined through thematic analysis supported by NVivo 14. The findings indicate that the intensity of Islamic Religious Education significantly influences adherence to Sharia business ethics (β = 0.412, p < 0.001). The internalization of religious values serves as a partial mediator (β = 0.287), while digital literacy functions as a positive moderator (β = 0.193). Qualitative findings reveal three major themes: (1) the contextualization of Islamic Religious Education content from a predominantly doctrinal approach toward entrepreneurship case-based learning; (2) ethical dilemmas within platform-based business ecosystems; and (3) the role of communities and mentorship in strengthening the consistency of ethical behavior. The study concludes that Islamic Religious Education has substantial potential to foster Sharia business ethics when delivered through an applied and contextual approach, integrated with digital literacy, and supported by a collaborative learning ecosystem. The contribution of this study lies in the development of an integrative model that connects value internalization theory, the psychology of religious education, and Islamic economics within the context of the millennial generation.